Whole person librarianship a social work approach to patron services - Zettervall, Sara K.; Nienow, Mary C. (Santa Barbara, California Libraries Unlimited, 2019)
"Highlights the connections rapidly being made between librarians and social workers and explains how to create those partnerships"--Provided by publisher.
Relationships are the new reference collection -- Partners in the library -- Social work students: "Living the dream" in the library -- Full-time library social workers -- Advocating for change -- Sustainable practice -- Appendix A: PIE chart worksheet -- Appendix B: Community needs assessment -- Appendix C: Learning contract template -- Appendix D: Sample intake form -- Appendix E: Sample staff survey -- Appendix F: Reflective practice worksheet.
Includes bibliographical references and index.
Keywords: Libraries and community -- United States; Public services (Libraries) -- United States; Public services (Libraries) -- United States -- Case studies; Librarians -- Professional relationships -- United States; Library employees -- Professional relationships -- United States; Social workers -- Professional relationships -- United States; Social service -- United States